New footprints of bondage number of connected unicyclic and line graphs - Priyatharsini, B.K. Keerthiga; Kumar, R. Senthil; Velammal, S. (2017)
The bondage number of a non-empty graph G is the smallest number of edges whose removal from G results in a graph with larger domination number of G. In this paper, we prove that the bondage number of connected unicyclic graphs is less than or equal to three. Also, we characterize the class of unicyclic graphs for which the bondage number of line graph of some standard graphs.
Keywords: Graph theory